ANALISA DAN PERANCANGAN APLIKASI DATA CENTER HARDWARE FORM MENGGUNAKAN TEKNOLOGI RFID (RADIO FREQUENCY IDENTIFICATION) - Yusrifa Luthfir Rachman; Fajar Septian (CV. Multi Kreasi Media, 2024)
Hardware management in data center is vital in the administration of an organization. In managing hardwares, it is necessary to have an effective, eficient and accurate registration system. Therefore, a good system which makes it easier is needed. The implementation of data center hardware management is in Bank CIMB Niaga. This study aims to identify part of the administrative system which needs to be improved and apply identified problem to make an easier workflow. The method used in this study is observation, interview and literature review. While, the development methode used is RAD (Rapid Application Development) using C# as the programming language and RFID (Radio Frequency Identification) Technology).